2019
DOI: 10.1002/cncr.32406
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter, open‐label, single‐arm study of anamorelin (ONO‐7643) in advanced gastrointestinal cancer patients with cancer cachexia

Abstract: Background Cancer cachexia is characterized by weight loss and is associated with increased morbidity and mortality in patients with cancer. Anamorelin (ONO‐7643; ANAM) is a novel and selective ghrelin receptor agonist that improves appetite, lean body mass (LBM), body weight, and anorexia. Methods This multicenter, open‐label, single‐arm study investigated the efficacy and safety of 100 mg anamorelin in 50 Japanese patients with advanced and unresectable gastrointestinal (colorectal, gastric, or pancreatic) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
91
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 41 publications
5
91
1
Order By: Relevance
“…Moreover, the alleviating effect of anamorelin on cachexia-related anorexia was maintained throughout the treatment period. Recently, anamorelin was further evaluated in patients with advanced gastrointestinal cancer and cachexia in a non-randomized single-arm study 51. This study also showed a positive effect of anamorelin on LBM, body weight, and anorexia that was comparable to the aforementioned data in patients with lung cancer.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Moreover, the alleviating effect of anamorelin on cachexia-related anorexia was maintained throughout the treatment period. Recently, anamorelin was further evaluated in patients with advanced gastrointestinal cancer and cachexia in a non-randomized single-arm study 51. This study also showed a positive effect of anamorelin on LBM, body weight, and anorexia that was comparable to the aforementioned data in patients with lung cancer.…”
Section: Resultssupporting
confidence: 57%
“…HGS, 6MWD, FatigueAtrioventricular block, rashHamauchi et al, Cancer. 20195150Advanced gastrointestinal cancer in Japanese (Cachexia)Not specified or combinedAnamorelin (12 weeks)Single-arm study with pre-post comparison1. LBM, BW, Appetite2.…”
Section: Resultsmentioning
confidence: 99%
“…1b). To this end, the ghrelin receptor agonist anamorelin has been investigated in Japanese patients with advanced gastrointestinal cancer with cachexia, resulting in gains in lean body mass and body weight [78].…”
Section: Nutritional Supportmentioning
confidence: 99%
“…In advanced colorectal cancer, on the other hand, few reports have investigated the prevalence and onset of cancer cachexia based on EPCRC criteria in patients after starting chemotherapy, whereas incidences of cancer cachexia before chemotherapy or during palliative care, and the correlations between cancer cachexia before chemotherapy and prognosis, toxicity, and QOL have been reported previously [13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%